(untitled) (Revista Brasileira Multidisciplinar, 2024)
Comparison dissolution profile between drugs is crucial to determining the interchangeability. This study compared the in vitro dissolution profiles of drugs containing 50 mg of lamotrigine in tablet form: three Brazilian pills (reference, generic, and similar) and three Peruvian pills (two similar and one generic) according to the official dissolution test guidelines. The results obtained from media with pH 1.2 and 4.5 indicate that all tested samples met the specified standards. However, in the dissolution medium at pH 6.8, only one of the lamotrigine tablets samples did not give a satisfactory result. These data helped me understand the possibility of interchangeability between Brazilian and Peruvian lamotrigine pills. They highlighted the impact of more research in this field to strengthen the discussions on guideline standardization across the countries to ensure the same bioavailability and efficacy for traveling patients.